Comparison Of Recruitment Systems Ukm (Student Activities Unit) Mapala (Nature Lover Students) Study Mapala Unived And Madyapala UMB - febriawan, Dandi; Hanila , Siti; Irwanto , Tito (Journal of Management, Economic, and Accounting, 2024)
The purpose of this research is to determine the comparison of the recruitment system for UKM (Student Activity Units) MAPALA (Nature Lover Students) STUDY MAPALA UNIVED AND MADYAPALA UMB. Based on the characteristics of the research, a research sample was obtained, namely 2 organizations, using the Census or Saturated sampling method. For this type of research, it is quantitative research, namely research in the form of interviews, observations and documentation in order to get the results of this research. The results of the research comparing the Recruitment System for UKM (Student Activity Units) MAPALA (Nature Lover Students) Study MAPALA UNIVED and MADYAPALA UMB are that in MAPALA UNIVED the stages in recruitment are different in conservation camps, whereas in MADYAPALA there is no such thing as a conservation camp, whereas the name of the activity in the two organizations is also different, for MAPALA UNIVED it is called DIKSAR while for MADYAPALA UMB Diklat Lalang, for people who can register in the two organizations there are differences, for MADYAPALA UMB for Engineering Faculty students there are special requirements whereas at MAPALA UNIVED There are no special requirements for each faculty at Dehasen Bengkulu University, for participant limits there is a semester limit when you want to register at MADYAPALA UMB, that is semesters 1-5 while at MAPALA UNIVED semesters 1-3, and for recruitment requirements at MAPALA UNIVED There is such a thing as a parent/guardian's permission letter and a statement of readiness to take part in Diksar, whereas in MADYAPALA UMB these requirements do not exist at all.